Risk for anxiety and implications for treatment: developmental, environmental, and genetic factors governing fear regulation. (22nd October 2013) - Hartley, Catherine A.; Casey, B.J.
Abstract : Anxiety disorders are the most common psychiatric disorders, affecting as many as 10% of youth, with diagnoses peaking during adolescence. A core component of these disorders is an unremitting fear in the absence of present threat. One of the most commonly used therapies to treat these disorders is exposure‐based cognitive behavioral therapy that identifies the source of the fear and anxiety and then desensitizes the individual to it. This treatment builds on basic principles of fear‐extinction learning. A number of patients improve with this therapy, but 40–50% do not. This paper provides an overview of recent empirical studies employing both human imaging and cross‐species behavioral genetics to examine how fear regulation varies across individuals and across development, especially during adolescence. These studies have important implications for understanding who may be at risk for anxiety disorders and for whom and when during development exposure‐based therapies may be most effective.